Long-term survival in patients treated with mechanical circulatory support for refractory out-of-hospital cardiac arrest. (2nd May 2022) - Moerk, S; Christensen, S; Boetker, MT; Tang, M; Terkelsen, CT
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Mechanical circulatory support (MCS) is used increasingly in the setting of refractory out-of-hospital cardiac arrest (OHCA). However, limited data exist on long-term survival. Purpose: To investigate the long-term outcome in patients receiving MCS compared to patients with return of spontaneous circulation (ROSC) at hospital admission. Methods: Retrospective, observational single centre study from 2015-2019. The study included all patients who achieved ROSC on admission and patients receiving MCS for refractory OHCA defined as either veno-arterial extracorporeal membrane oxygenation or Impella support. Kaplan-Meier survival analysis were performed to evaluate long-term survival in both groups and compared with the log-rank test. Results: A total of 698 patients with ROSC on admission and 101 patients receiving MCS were included. Acute myocardial infarction was the most common aetiology of arrest in both groups. There were no differences in witnessed arrest, bystander cardiopulmonary resuscitation or initial presenting rhythm. Low-flow time was substantially longer in the MCS group compared to the ROSC group (median 105 (IQR, 94-123) minutes versus median 15 (IQR, 8-22) minutes, p < 0.001). The 5-day mortality rate was 63% in the MCS group versus 24% in the ROSC group. Long-term survival from day 6 to day 90 was 71% in the MCS group and 83% in the ROSC group, p = 0.072. Conclusions: In conclusion, the risk of death within the first 5 days was higher for OHCA patients treated with MCS than in patients with ROSC on admission. Among patients surviving the first 5 days, 90-day mortality was low in both groups.